2010
DOI: 10.4028/www.scientific.net/kem.436.75
|View full text |Cite
|
Sign up to set email alerts
|

The FFC Cambridge Process for Production of Low Cost Titanium and Titanium Powders

Abstract: The current status and recent advancements in the use of the FFC Cambridge process for the production of low cost titanium and titanium powders is presented. This will include an overview of the process, current and future process equipment and recent results in terms of chemistry, structure and properties of powder and consolidated product. The future direction and activities for the FFC Cambridge process will also be briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…This morphology results from the reconstructive phase transformations during the complex kinetic pathway for deoxidation of TiO 2 , and the in situ sintering of the formed titanium fine particles, 50,51 which can be pulverised to powders for further treatments or applications. 52 …”
Section: Concept Of the Ffc-cambridge Processmentioning
confidence: 99%
See 1 more Smart Citation
“…This morphology results from the reconstructive phase transformations during the complex kinetic pathway for deoxidation of TiO 2 , and the in situ sintering of the formed titanium fine particles, 50,51 which can be pulverised to powders for further treatments or applications. 52 …”
Section: Concept Of the Ffc-cambridge Processmentioning
confidence: 99%
“…This potential was investigated by Metalysis TM (Rotherham, UK) through direct grinding of the electrolytic titanium, hydriding-grinding-dehydriding, and fusion and gas atomisation. 52 Recently, Metalysis TM also attempted direct electro-reduction of natural rutile powders to titanium powders. 20 Following plasma spheroidisation (see Fig.…”
Section: Incorporation With the Advanced Manufacturing Conceptsmentioning
confidence: 99%
“…From an end-product quality perspective, there is little published information to date on the quality of the powders produced by using the FFC process. Bertolini et al [82] reported that powder produced by the FFC process at a multiple kg scale had 0.29 wt-% O, 0.07 wt-% C, 0.014 wt-% Fe, 0.13 wt-% Ca and 0.06 wt-% Cl, provided as an example of the composition of Ti powder made from pure TiO 2 using the FFC process. However, the report does not necessarily represent the best capability of the process, which is still under development.…”
Section: Electrochemical Processesmentioning
confidence: 99%
“…However, the process is expensive because reduction and distillation require a long time, production is intermittent, and consumes large amounts of energy during the electrolysis step. A simpler and more compact singlestep would be desirable for the direct conversion of TiO 2 or TiCl 4 into titanium in order to achieve high productivity at low energy costs. 1,2 The direct electrolysis of TiO 2 , which is a novel method of electro-deoxidization, was first realized in the FFC Cambridge process in 2000.…”
Section: Introductionmentioning
confidence: 99%
“…This process consists of three steps, which include: the conversion of TiO 2 to TiCl 4 , the subsequent reduction of TiCl 4 to titanium by liquid Mg, and the electrolysis of the MgCl 2 byproduct. However, the process is expensive because reduction and distillation require a long time, production is intermittent, and consumes large amounts of energy during the electrolysis step.…”
Section: Introductionmentioning
confidence: 99%